ANALISIS NILAI KARAKTER BERBASIS SEMIOTIKA ROLAND BARTHES DALAM FILM ANIMASI TOY STORY 2 DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER DI SD - Sigit , Asep; Hidayat , Syarip (ATTA`DIB, 2024)
This research aims to describe the character values ​​in the animated film Toy Story 2 and explain their relevance to character education in elementary school. This research is a type of qualitative research because the data collected is not in numerical form. Data collection uses documentation methods for primary data sources, namely the animated film Toy Story 2 and secondary data literature studies regarding character values. After the data was collected, in examining the meaning and signs in the animated film Toy Story 2 using Roland Barthes' semiotics, it was then relevant to character education of hard work, creativity, respect for achievement, discipline, communicative/friendly and social care. Based on the research results, the character values ​​in the animated film Toy Story 2 were found to be 9 character values, namely having a high imagination, having creative ideas, respecting other people's achievements, caring for friends, helping each other, never giving up, being orderly, friendship, and cooperate. Then the character values ​​in the animated film Toy Story 2 have relevance to creative character education, respect for achievement, hard work, discipline, friendship/communicativeness, and social care.